2018
DOI: 10.3892/etm.2018.6543
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the proposal of paediatric virology: An interview with Professor Tina Dalianis, Professor of Tumour Virology at Karolinska Institutet

Abstract: Professor Tina Dalianis, Professor of Tumour Virology at Karolinska Institutet in Stockholm, Sweden, is a well-known virologist with a strong international reputation and seminal contributions in tumour virology in the fields of human papillomaviruses (HPVs) and polyomaviruses. According to Professor Dalianis, over the past decades virology has significantly contributed to the understanding of many infectious diseases in medicine. In addition, quite a few antiviral therapies have been developed in recent years… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 17 publications
(9 reference statements)
0
4
0
Order By: Relevance
“…Besides, HPV can be transmitted vertically from the mother to the child during delivery which may result in neonatal and congenital, oral, or conjunctival lesions. 18,19 Anogenital warts in immunsupression: Immuncompromised individuals have a higher risk of malignant transformation and higher risk of coinfection with more than one HPV type and also have a higher viral load. AGWs are larger and more treatment resistant with higher recurrence rates.…”
Section: Special Conditionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides, HPV can be transmitted vertically from the mother to the child during delivery which may result in neonatal and congenital, oral, or conjunctival lesions. 18,19 Anogenital warts in immunsupression: Immuncompromised individuals have a higher risk of malignant transformation and higher risk of coinfection with more than one HPV type and also have a higher viral load. AGWs are larger and more treatment resistant with higher recurrence rates.…”
Section: Special Conditionsmentioning
confidence: 99%
“…Cervical cancer: High-risk HPV subtypes (HPV 16 and HPV 18) are the causes of approximately 70% of invasive cervical cancer and it is estimated that 500,000 cases of cervical cancer occur each year worldwide. [9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24] A study of paraffin-embedded samples of 10,575 cases of cervical cancer demonstrated that the most common HPV types were 16,18,31,33,35,45,52, and 58; HPV types 16 and 18 represented 71% of the cases overall. 25 Other anogenital cancers: Vaginal, vulvar, penile and anal cancers and their precancerous precursors such as vulvar intraepithelial neoplasia (IN), penile IN, anal IN are other associated neoplasies.…”
Section: Neoplasiamentioning
confidence: 99%
“…On October 10th, 2015, he presented the '2015 Paediatric Virology proposal' (14), which, to date, has attracted the critical interest of several leading experts in the scientific fields of Neonatology, Paediatrics, PID and Virology (15). Although this debate has already tagged difficulties, challenges and limitations on the role of Paediatric Virology as a separate paediatric subspecialty, the '2015 Paediatric Virology proposal' has been evaluated as 'a call for innovation in paediatric education' (16) and 'an educational goal for advanced academic excellence' (17); the potential value of Paediatric Virology subspecialists in the future has undoubtedly been accepted (16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28).…”
Section: Introductionmentioning
confidence: 99%
“…In Europe, as it will be highlighted in the context of the ‘4th Workshop on Paediatric Virology’ ( 6 9 ), paediatric virologists are definitely required and should exist in the tertiary centres of each country, having a strategically principal role, both clinical and academic, in the fight against viral infections occurring in neonates and children. In the UK, for example, with a population which grew to an estimated 65.1 million in 2015, paediatric virologists of the National Health System (NHS) should be located in UK reference centres, providing they have the capacity to provide comprehensive coverage for the UK between them.…”
mentioning
confidence: 99%